My perfectionism drives me to be a cyborg: moderating role of internal locus of control on propensity towards memory implant - Ashraf, Sadat Ahabdzadeh; Wu, Shin Ling *; Lee, Kam Fong; Ong, Fon Sim; Deng, Ruolan (Wiley, 2023)
Intention to use memory implants for non-therapeutic purposes has recently received attention among researchers. The present study examined perfectionism with two dimensions namely personal standards (PS) and evaluative concerns (EC) as possible dispositional factors associated with the intent to use memory implants. This study also examined the moderating role of internal locus of control (LOC) on the relationship between the dimensions of perfectionism and the intention to use memory implants. Employing a cross-sectional design, this study collected data on PS, EC, internal LOC and intention to use memory implants from a purposive sample of 686 Spanish university students aged between 18 and 28 years old (M = 21.88, SD = 2.40, males = 361, females = 325). Results showed that both PS and EC perfectionism have positive relationships with the intent to use memory implants. Internal LOC is also found to be strengthening the relationship between PS and the intent to use memory implants. These findings yield implications for those pushing forward the acceptance of human–machine hybrid and for those concerned about the detrimental consequences of such artificially formulated changes in humankind.